(3ebGdI aj cTa GdTHgI GdJi YQVJ dLeGYI eef fSH Edi Ydhe GdJYGdje Ydi EbdjOS aj GdTcd GdQGHY YTQ ef GdebGdI GdKGfjI YTQ ef cJGH GdCUhds - (3fLe GdOjf CHh GdaJhM CMeO Hf eMeO Hf GdSQj hcGf jYQa HGHf GdUdGM,J (B548 (3g` s
(3ChdgG (B:s
(3bGd Efi deG QCjJ LeGYI eef GfJei Edi Ydhe GdJYGdje bO Xd Yf age GdeYfi GdPi GSJYedg GbdjOS ai GdTcd GdQGHY YTQ ef GdebGdI GdKGfjI YTQ hGHOd bhdg ajg Hbhd BNQ RGO ajg s
(3BNQgG (B:s
(3LgI CNQi ef ZjQ MGLI Edi GdebOeI GdJi bOefGgG ZjQ EfgG JMJGL Edi ZehV JUhQ Edi Cf jJbOegG HYV GdNhGU GdePchQI ai GdebGdI GdChdi ef cJGH KGhPhSjhS s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfi YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs